Ecological Citizenship Based on Green Constitution through Environmental Education - Pudjiastuti, Sri Rahayu; Saryono; Hardianto, Lutfi (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Problems associated with green constitution-based ecological citizenship include challenges in law enforcement, conflicts between economic and environmental interests, social inequality, and difficulties in encouraging adequate public participation. The purpose of this research is to see how the green constitution can help raise environmental awareness in Indonesia through education. The research found, using a qualitative approach and literature analysis techniques, that environmental education should be part of the national curriculum. The results show that education based on environmental principles can make people more involved in environmental protection.